Political economy of labor market institutions in a globalised era - Sumon Kumar Bhaumik; Richard Frensch; Stephan Huber (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2021)
The paper extends the literature on the political economy of labor market institutions by developing a framework in which owners of capital can benefit from both greater labor market flexibility and better rule of law. Their choice of location of manufacturing centres can, therefore, by influenced both by reduction in expropriation that is associated with better rule of law and greater bargaining power vis-à-vis workers by way of greater labor market flexibility. It follows that where owners of capital are better placed to influence government choices of these institutions, labor market flexibility is influenced by both labor market institutions intensity of exports and as well as rule of law intensity of exports. These predictions are borne out by a cross-country empirical analysis.
Keywords: D72; J41; 330; Labor market institutions; Political economy; Globalisation